Evaluating Category Performances in Category Management: an Empirical Regional Study - Alexakis, Dimitrios; Erdiller, Ozgur; Papamanousakis, Georgios (My University, 2012)
This paper aims to identify regional properties of product categories and consumer perception and preferences of relevant grocery retailing product categories, in the Greek Island of Crete and the three cities. The dataset for this research consists of a sample of 2,000 consumers, distributed in three major cities in Crete. Ten product hyper-categories consisting of 102 product categories were identified through the regional grocery retailers. The collected data is analysed initially by rank-order and product-moment correlation. Afterwards, categorical principal component analysis was applied for clustering customer segments with similar demographic and consumption patterns. The study introduces a regional overview of category management practices and provides a detailed identification of the grocery retail market. This study also shows the mainstream profile in a relatively small regional retail market
Keywords: Greece; Consumers; Management; Market segmentation